Análisis crítico jurídico de la responsabilidad penal del médico en delitos de comisión por omisión - Coello Calles, Paola Anahí (2025)
ABSTRACT Criminal medial liability for omission es a relevant topic in legal and medical fields due to its impact on patients’ safety and the legal consequences for the healthcare professionals. In Ecuador, the increase in cases of medical negligence has affected the quality of care and people’s lives. This study critically analyzes the legal medical liability in crimes of commission by omission in healthcare facilities in the province of Pastaza, addressing the factors that lead to the omission and its legal implications. Through a mixed approach, the study combines theoretical and empirical research, becoming descriptive, systematic, legal and non-experimental. The applied methods were analytical-synthetical, historical-logical, hermeneutical, exegetical, sociological, and legal-analogical. Empirically, interviews were conducted and juridical case analysis with a sample of 30 physicians and 30 experts in criminal law from Pastaza, using techniques such as bibliographic records and semi- structured interviews. The results revealed that physicians and lawyers lack specific training which generates gaps in the resolution of cases. Medical omission, defined as inaction in the face of a normative duty, encounters legal obstacles, lack of cooperation and hospital overcrowding. Although Article 146 of COIP regulates these crimes, it excludes non-lethal harm, and the lack of knowledge about lex artis increases legal uncertainty. KEYWORDS: criminal liability, medical practice, omission, crimes of commission by omission